2012
DOI: 10.1261/rna.032680.112
|View full text |Cite
|
Sign up to set email alerts
|

In vivo structure–function analysis of human Dicer reveals directional processing of precursor miRNAs

Abstract: Dicer is an RNase III family endoribonuclease and haploinsufficient tumor suppressor that processes mature miRNAs from the 59 (5p) or 39 (3p) arm of hairpin precursors. In murine Dicer knockout fibroblasts, we expressed human Dicer with point mutations in the RNase III, helicase, and PAZ domains and characterized miRNA expression by Northern blot and massively parallel sequencing of small RNAs. We report that inactivation of the RNase IIIA domain results in complete loss of 3p-derived mature miRNAs, but only p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
124
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(142 citation statements)
references
References 32 publications
15
124
1
2
Order By: Relevance
“…We also analysed the miRNA expression data from the TCGA endometrial cancer cohort, and observed similar results (see supplementary material, Figure S5): the entire 5p miRNA population was reduced in tumours with DICER1 hotspot mutations (mean ± SE = 54.9 ± 4.7; n = 6) compared to either tumours with DICER1 non-hotspot mutations (mean ± SE = 66.7 ± 3.1; n = 14; p = 0.052) or tumours without DICER1 mutations (mean ± SE = 67.7 ± 0.5; n = 375; p = 0.001). However, the reduction of 5p miRNAs in tumours with hotspot mutations was not as drastic as in DICER1-null cell lines that express hotspot mutants [4,12], which may be due to other confounding factors in tumours, such as the presence of WT allele, DICER1 variant allele frequency, additional genetic aberrations, intratumour heterogeneity, tumour cell content and cell-free circulating miRNAs.…”
Section: Mature Mirna Expression In Tumours With Dicer1 Hotspot Mutationmentioning
confidence: 87%
See 2 more Smart Citations
“…We also analysed the miRNA expression data from the TCGA endometrial cancer cohort, and observed similar results (see supplementary material, Figure S5): the entire 5p miRNA population was reduced in tumours with DICER1 hotspot mutations (mean ± SE = 54.9 ± 4.7; n = 6) compared to either tumours with DICER1 non-hotspot mutations (mean ± SE = 66.7 ± 3.1; n = 14; p = 0.052) or tumours without DICER1 mutations (mean ± SE = 67.7 ± 0.5; n = 375; p = 0.001). However, the reduction of 5p miRNAs in tumours with hotspot mutations was not as drastic as in DICER1-null cell lines that express hotspot mutants [4,12], which may be due to other confounding factors in tumours, such as the presence of WT allele, DICER1 variant allele frequency, additional genetic aberrations, intratumour heterogeneity, tumour cell content and cell-free circulating miRNAs.…”
Section: Mature Mirna Expression In Tumours With Dicer1 Hotspot Mutationmentioning
confidence: 87%
“…This is consistent across both the TCGA dataset (7/304) and our own local tumour bank (6/290; see supplementary material, Tables S1, S7). DICER1 hotspot mutations, although rare, were also identified in brain, colorectal and thyroid cancers (see supplementary material, TableDICER1 hotspot mutations in endometrial cancer 223 tumourigenesis beyond the spectrum of rare paediatric cancers [8][9][10][11][12][13][15][16][17][18]. DICER1 hotspot mutations and subsequent miRNA/mRNA dysregulation may therefore constitute a common oncogenic pathway in a small subset of endometrial tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human FLAG‐Dicer in pCAGGS [a gift from Phil Sharp, Addgene #41584 (Gurtan et al , 2012)] was transfected into HEK293T cells using Lipofectamine 2000. Twenty‐eight hours post‐transfection, cells were lysed in lysis buffer [30 mM Tris pH 6.8, 50 mM NaCl, 3 mM MgCl 2 , 5% glycerol, 0.4% NP‐40 and protease inhibitors (Roche)], and the lysate was cleared by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant SFV‐Rluc was generated using the infectious DNA clone pCMV‐SFV(3H)Rluc as previously described (Tamberg et al , 2007). pCAGGS‐Flag‐hsDicer was a gift from Phil Sharp (Addgene plasmid # 41584) (Gurtan et al , 2012). All primers used to generate pLHCX‐HA‐mAgo2 WT and pLHCX‐HA‐mAgo2 D597A are listed in Appendix Table S1.…”
Section: Methodsmentioning
confidence: 99%